Preparation method and application of dual-network piezoelectric induction hydrogel with piezoelectric effect
By preparing a piezoelectric inductive hydrogel with a dual-network structure, the shortcomings of traditional hydrogels in terms of mechanical properties and anti-infection are overcome, achieving comprehensive regulation and antibacterial effects in the treatment of infected wounds, and providing a more stable and efficient treatment solution.
Patent Information
- Application Number
- CN202511562445.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-29
- Publication Date
- 2026-01-23
AI Technical Summary
Existing materials for treating infected wounds have significant shortcomings in terms of insufficient mechanical properties, lack of piezoelectric properties, and anti-infection function. They are difficult to effectively regulate cell migration, angiogenesis, and nerve repair in complex wound environments, and there are risks of excessively rapid release, local toxicity, and drug resistance.
A piezoelectric-inductive hydrogel with a dual-network structure is formed by cross-linking ACG and GelMA and adding BTO nanoparticles to create a hydrogel with piezoelectric properties. Combined with anti-infection function, it achieves mechanical stability and electrical signal modulation.
It significantly enhances the mechanical strength and stability of the material, can generate electrical signals under external force to promote cell proliferation, migration and angiogenesis, and at the same time has excellent antibacterial properties, reducing the risk of infection, and realizing the triple functions of physical support, electrical stimulation regulation and anti-infection.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of hydrogel technology, and more specifically, to a method for preparing and applying a dual-network piezoelectric inductive hydrogel with piezoelectric effect. Background Technology
[0002] Current materials for treating infected wounds mainly employ conventional hydrogel dressings, whose mechanisms of action largely rely on providing a moist healing environment, controlling drug release, and isolating external contaminants. However, these materials have significant shortcomings in complex wound environments: First, their mechanical properties are weak, often exhibiting insufficient tensile strength and compressive modulus, making them unable to withstand long-term coverage and external mechanical stress, leading to deformation or rupture, which is detrimental to the long-term treatment of chronic wounds. Second, traditional single-polymer hydrogels are mostly inert materials, lacking piezoelectric properties, and cannot convert external mechanical stimuli into electrical signals, thus failing to effectively regulate processes such as cell migration, angiogenesis, and nerve repair, limiting their intervention and regeneration-promoting effects on the wound's electrophysiological microenvironment. Third, existing hydrogel systems struggle to simultaneously address anti-infection and tissue regeneration functions. Although loading antibiotics, metal ions, or antimicrobial peptides can achieve antibacterial effects to some extent, they generally suffer from excessively rapid release rates, local toxicity, and the risk of drug resistance. Meanwhile, single-functional hydrogels lack comprehensive regulation of cell proliferation, angiogenesis, and tissue repair. The aforementioned defects mainly stem from the loose structure, high water content, low cross-linking density, and simple material design of traditional hydrogel networks, resulting in insufficient mechanical stability, lack of electrical functions, and poor functional integration.
[0003] Therefore, there is an urgent need in this field for a hydrogel material that combines excellent mechanical strength, stable piezoelectric effect, and comprehensive anti-infection function. Summary of the Invention
[0004] To address the aforementioned problems, this invention provides a dual-network piezoelectric sensing hydrogel with piezoelectric effect. This hydrogel significantly enhances the mechanical properties and structural stability of the material through its dual-network structure, overcoming the shortcomings of traditional hydrogels such as excessive deformation and insufficient mechanical properties. Simultaneously, by introducing functional components with piezoelectric properties at the molecular or composite structure level, the material can generate stable electrical signals under external forces, thereby improving the local electrophysiological environment of the wound, promoting cell proliferation, migration, and angiogenesis, and accelerating tissue repair. Furthermore, while achieving electrical regulation, the hydrogel of this invention can also possess anti-infection functions, avoiding the limitations of single drug loading or passive protection strategies, reducing the risk of drug resistance and toxic side effects, and achieving a synergistic effect of antibacterial and regenerative effects.
[0005] To achieve the above-mentioned objectives, this application adopts the following technical solution: In a first aspect, this application provides a method for preparing a dual-network piezoelectric inductive hydrogel with piezoelectric effect, comprising the following steps: Using ACG and GelMA as base materials, MBA as a crosslinking agent, and a photoinitiator, free radical polymerization is initiated by ultraviolet light to form a precursor solution. BTO nanoparticles were dispersed in the system, and after thorough mixing, the dual-network piezoelectric hydrogel ACG-Gel-BTO was prepared by curing.
[0006] Furthermore, the ACG is obtained by the following preparation method: glycine is dissolved in potassium hydroxide solution and cooled in an ice-water bath. Acryloyl chloride is then slowly added to the mixture, stirred at room temperature, washed, pH adjusted, extracted, dried, and concentrated to obtain the ACG.
[0007] Furthermore, the BTO is obtained by the following preparation method: Tetrabutoxytitanium was dissolved in anhydrous ethanol, and after thorough mixing, an ammonia solution was quickly added and the mixture was stirred vigorously to hydrolyze the tetrabutoxytitanium and form a white sol. According to the predetermined barium-titanium ratio, barium hydroxide monohydrate was weighed and dissolved in deionized water. The dissolved barium hydroxide solution was mixed with the above white sol and stirred thoroughly at room temperature. Triethanolamine was added and reacted at a temperature of 140~200℃. After the reaction was completed, the mixture was washed several times with glacial acetic acid, deionized water and anhydrous ethanol, dried and ground to obtain BTO powder.
[0008] Furthermore, the BTO powder is also subjected to heat treatment, the heat treatment step being: calcination at 800~1200℃ and cooling in a furnace to obtain heat-treated BTO powder.
[0009] Furthermore, the feeding ratio of ACG, GelMA, MBA and photoinitiator I2959 is 0.1g:0.02g:0.3mL:0.005g.
[0010] Furthermore, the amount of BTO added, calculated as a weight percentage, is 0.25~0.75% of the precursor solution.
[0011] In a second aspect, this application provides a dual-network piezoelectric sensing hydrogel with piezoelectric effect, which is prepared by any of the preparation methods described in the first aspect.
[0012] Thirdly, this application provides the application of the dual-network piezoelectric inductive hydrogel of the second aspect in the preparation of infectious wound healing drugs.
[0013] In summary, this application has the following beneficial effects: Compared with existing technologies, the dual-network piezoelectric hydrogel prepared in this invention exhibits significant advantages. Its dual-network structure significantly enhances the material's mechanical strength and stability, effectively solving the problems of easy deformation and limited long-term application of traditional hydrogels. Simultaneously, the incorporation of BaTiO3 nanoparticles endows the hydrogel with piezoelectric properties, enabling it to generate electrical signals under external force, thereby positively regulating processes such as cell proliferation, migration, and angiogenesis. Furthermore, this hydrogel maintains a moist wound environment while possessing excellent antibacterial properties, effectively inhibiting bacterial growth and reducing the risk of infection. The material also exhibits controllable degradation characteristics, eliminating the need for secondary removal. In summary, the hydrogel of this invention combines physical support, electrical stimulation regulation, and anti-infection functions in the treatment of infected wounds, and its overall performance is significantly superior to existing single-function hydrogel materials. Attached Figure Description
[0014] Figure 1 : Schematic diagram of the synthesis mechanism of AB-Gel hydrogel; Figure 2 : A schematic diagram of the macroscopic synthesis of AB-Gel hydrogel; Figure 3 : FTIR schematic diagram proving successful crosslinking of AB-Gel hydrogel; Figure 4 Microscopic double-network structure of AB-Gel hydrogel as captured by SEM; Figure 5 Macroscopic morphology and tensile / compression properties of AB-Gel hydrogel; Figure 6 Tests on the piezoelectric properties of AB-Gel hydrogels with different concentrations of BTO incorporated; Figure 7 Tests on the adhesiveness and self-healing properties of AB-Gel hydrogel; Figure 8 Biocompatibility testing of AB-Gel hydrogel; Figure 9 AB-Gel hydrogel promotes ROS generation detection; Figure 10 AB-Gel hydrogel in vitro antibacterial assay - bacterial plate coating test; Figure 11 AB-Gel hydrogel in vitro antibacterial assay - bacterial live / dead fluorescence staining experiment; Figure 12 AB-Gel hydrogel in vitro antibacterial and biofilm disruption experiments; Figure 13 Application of AB-Gel hydrogel biotechnology in promoting the healing of infected wounds. Detailed Implementation
[0015] The technical solutions and effects of this application will be further described in detail below with reference to the embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are merely for explaining the invention and are not intended to limit the invention.
[0016] Preparation Example: Preparation of hydrogel substrates containing acryloylglycine (ACG), gelatin (GelMA), and barium titanate nanoparticles (BaTiO3, BTO). (1) Preparation method of ACG: Dissolve 4.5 g glycine (60 mmol) in 60 mL of 2 M potassium hydroxide solution. Cool the mixture in an ice-water bath at 0 °C for 10 minutes. Add 6 mL of acryloyl chloride (73.6 mmol) dropwise to the mixture using a dropping funnel.
[0017] After stirring at room temperature for 3 hours, the product was washed twice with diethyl ether, and then the aqueous phase was acidified to pH 2.0. The product was extracted three times with ethyl acetate. After drying the organic phase with magnesium sulfate, the residue was concentrated by rotary evaporation to give a white solid product in 74% yield.
[0018] (2) GelMA preparation method: Add 15g of gelatin to ddH2O at 40℃ and stir until fully dissolved. Then, add 15mL of methyl methacrylate (MA) dropwise at a rate of 0.5mL / min. Stir at 37℃ for 24h, and dialyze against ddH2O at room temperature for 4 days, changing the solution twice a day. Freeze-dry the resulting liquid for later use.
[0019] Dissolve the lyophilized product in PBS at a concentration of 5% at 37°C until fully dissolved, and add 1.5 mg / mL of photoinitiator I2959. When using, take out the mixed precursor solution and cure it under 365 nm ultraviolet irradiation.
[0020] (3) Preparation method of BaTiO3: Weigh 10 mmol of tetrabutoxytitanium [(C4H9O)4Ti] and place it in a Teflon cup lined with 50 mL of polytetrafluoroethylene (PTFE). Add 4 mL of anhydrous ethanol to dissolve it. After the tetrabutoxytitanium and anhydrous ethanol are thoroughly mixed, quickly add 1.5 mL of ammonia solution (25-28% NH4OH) and stir vigorously to hydrolyze the tetrabutoxytitanium, forming a white sol.
[0021] Weigh out 15 mmol of barium hydroxide monohydrate [Ba(OH)₂·H₂O] according to the predetermined barium / titanium ratio (Ba / Ti = 1.5) and dissolve it in 5 mL of deionized water. Mix the dissolved barium hydroxide solution with the above white sol, stir thoroughly at room temperature, and then transfer to a hydrothermal reactor. Before shutting off the hydrothermal reactor, add 1.12 g of triethanolamine (TEOA) to the mixture according to the experimental conditions. The reaction time is set to 0.5 h–48 h, and the reaction temperature range is 140 °C–200 °C.
[0022] After the reaction was complete, the supernatant was transferred to an alkaline solution container. The resulting hydrothermal product was washed repeatedly with glacial acetic acid, deionized water, and anhydrous ethanol (9000 rpm, 5 min) to thoroughly remove excess BaO and BaCO3. It was then dried in an oven at 80 °C for 4 h and ground to obtain BaTiO3 powder.
[0023] A small amount of BaTiO3 powder was placed in a crucible and calcined at 800℃-1200℃ for 4 hours, and then cooled in a furnace to obtain heat-treated BaTiO3 powder.
[0024] Example 1: Preparation and performance testing of AB-Gel dual-network piezoelectric inductive hydrogel Step-by-step instructions: This hydrogel was prepared using a photoinitiated free radical polymerization process. The specific steps are as follows: (1) Preparation of precursor solution: Taking 1 mL hydrogel precursor solution as an example, 0.1 g ACG (10%) and 0.02 g gelatin (Gel) are first used as base materials and dissolved in 0.7 mL ddH2O and 0.3 mL 0.1% methylenebisacrylamide (MBA), and 5 mg photoinitiator I2959 is mixed in.
[0025] (2) After thoroughly mixing by vigorous shaking to ensure complete dissolution, add different weights of BTO nanoparticles (2.5mg / 0.25%, 5.0mg / 0.50%, 7.5mg / 0.75%) and sonicate at 37°C for 15-30 minutes to ensure thorough mixing.
[0026] (3) Finally, the hydrogel is cured using a 365nm wavelength ultraviolet light curing lamp. Before cell experiments, the hydrogel needs to be filtered and sterilized to ensure a sterile environment.
[0027] (4) Mechanical properties, piezoelectric properties, biocompatibility, ROS and antibacterial properties of AB-Gel hydrogel were tested.
[0028] Experimental results: (1) such as Figure 1 , Figure 2 As shown, ACG and Gel are cross-linked by MBA to form a precursor solution of hydrogel. Different concentrations of BTO nanoparticles are mixed into it, and after being irradiated by ultraviolet light (UV), a solid AB-Gel hydrogel is formed.
[0029] (2) For example Figure 3 As shown, FTIR infrared spectroscopy reveals that ACG and Gel are successfully crosslinked via amide bonds and hydrogen bonds.
[0030] (3) The microstructure of AB-Gel hydrogel was verified by applying SEM, and the results are as follows: Figure 4 The AB-Gel hydrogel exhibits an alternating horizontal and vertical double network structure, with BTO distributed within it.
[0031] (4) such as Figure 5 As shown, AB-Gel hydrogel is white in appearance and exhibits good tensile and compressive properties.
[0032] (5) such as Figure 6 As shown, AB-Gel exhibits good piezoelectric properties, and the microcurrent generated by the AB-Gel hydrogel increases with the increase of BTO concentration.
[0033] (6) AB-Gel hydrogels exhibit strong viscosity, such as Figure 7 As shown, the hydrogel can withstand the tensile force of a 60g weight and can self-heal and withstand the pull of its own weight within 15 minutes.
[0034] (7) After comprehensive experiments on mechanical and piezoelectric properties, we selected 0.5% BTO concentration as the optimal performance of AB-Gel hydrogel for subsequent experiments. Its cytotoxicity was within acceptable limits. Figure 8 As shown.
[0035] (8) Excessive ROS generation is an important mechanism leading to bacterial death. To verify the ability of AB-Gel to increase the ROS level in the surrounding environment through the piezoelectric effect, the ability of AB-Gel to generate ROS was tested using a ROS detection kit. The experimental results are as follows: Figure 9 As shown.
[0036] Example 2: Antibacterial performance testing of AB-Gel dual-network piezoelectric inductive hydrogel 1. Bacterial plate coating experiment: (1) Antibacterial experiments were conducted using Gram-negative bacteria E. coli and Gram-positive bacteria MRSA. 500 μl of the prepared bacterial suspension (10 8CFU / mL was added to 500 μl of each cell culture medium and placed in 24-well cell culture plates. A negative control group (Ctrl group) was established. The AB-Gel group received ultrasound irradiation (1.5 W / cm²). 2 (1 MHz, 10 min), and then the 24-well plate was incubated in a 37°C incubator for 2 hours.
[0037] (2) After incubation, the bacterial suspension was separated from the hydrogel surface using sterile PBS and diluted 100-fold (10 6 (CFU / mL). A 24-hour plate-spreading culture was then performed, and the bacterial survival rate on each agar plate was observed and recorded.
[0038] 2. Bacterial live / dead fluorescent staining experiment: (1) E. coli and MRSA were cultured to the logarithmic growth phase, and then the bacterial concentration was diluted to 10 with physiological saline. 6 CFU / mL. Place a bacterial slide at the bottom of a 24-well plate, add 300 μl of diluted bacterial suspension to each well, and incubate at 37°C for 24 hours.
[0039] (2) The bacterial suspension in each well was aspirated and incubated for 1 hour, with the AB-Gel group receiving an additional 10 minutes of sonication.
[0040] (3) Subsequently, the bacterial slides were rinsed twice with PBS (1×) solution (5 minutes each time). The bacteria were then stained using a bacterial viability / death staining kit. In short, an appropriate amount of viability / death staining working solution (100×) was mixed with the bacterial slides and incubated at 37°C for 15 minutes in the dark. After staining, the staining effect was observed under a confocal microscope.
[0041] 3. Experiment on bacterial biofilm disruption: (1) Suspend E. coli and MRSA (10 6 CFU / mL was seeded into 24-well cell culture plates and incubated for 72 hours to form a biofilm on the well surface.
[0042] (2) After confirming biofilm formation, gently remove the supernatant and add 500 μL of GelMA, A-Gel, and AB-Gel solutions to each well, and set up a negative control group (Ctrl). After incubating at 37°C for 2 hours, aspirate the treatment solution and wash the well plate with PBS.
[0043] (3) Fix the biofilm with anhydrous methanol at room temperature for 15 minutes, remove the methanol, air dry, and stain with crystal violet for 20 minutes. After removing excess dye, wash twice with PBS and obtain representative images.
[0044] Experimental results: (1) such as Figure 10 As shown in the bacterial plate coating, both the AB-Gel group and the A-Gel hydrogel without BTO showed good antibacterial properties against E. coli and MRSA.
[0045] (2) To better determine whether the increased ROS due to the piezoelectric effect of BTO gives AB-Gel better antibacterial properties, we conducted a bacterial live / dead staining experiment at a higher concentration. The experimental results are as follows: Figure 11 As shown, compared to A-Gel, AB-Gel exhibits superior antibacterial properties in environments with higher bacterial concentrations, which proves that the antibacterial properties of AB-Gel benefit from its piezoelectric effect, which increases the ROS of the surrounding environment.
[0046] (3) In order to better simulate the bacterial biofilm environment of chronically infected wounds, we tested the biofilm disruption ability of AB-Gel. The experimental results are as follows: Figure 12 As shown, compared to the other three groups, AB-Gel more thoroughly disrupted the biofilms of the two bacteria.
[0047] Example 3: Application of AB-Gel dual-network piezoelectric inductive hydrogel in the healing of infected wounds The specific operating procedure is as follows: (1) An infectious wound model was constructed using 6-week-old SD rats. Each rat was anesthetized and shaved. Then, a full-thickness circular skin incision with a diameter of 15 mm was made on each side of the back using a skin trephine.
[0048] (2) Take 30 μL of a concentration of 10 6 Inducing infection by injecting a CFU / mL suspension of methicillin-resistant Staphylococcus aureus (MRSA) into the wound site. Twenty-four hours later (day 0), successfully infected rats were randomly divided into four groups: negative control (Ctrl), GellMA group, A-Gel group, and AB-Gel group. The AB-Gel group received 10 minutes of ultrasound irradiation (power 1.5 W / cm²). 2 (frequency 1 MHz).
[0049] (3) To monitor the healing process of infected wounds, photographs were taken on days 0, 3, 7, and 14. The formula for calculating the wound closure rate is: Wound closure rate (%) = (Wound area on day 0 - Wound area on a specific date) / (Wound area on day 0) × 100.
[0050] Experimental results: like Figure 13As shown, the wound healing in the AB-Gel group was better than that in the other three groups on days 3, 7 and 14 after treatment, and the final wound healing rate was higher on day 14. Moreover, no obvious signs of bacterial infection were observed in the wound area of the rats. This result proves that AB-Gel hydrogel plays a promoting role in the healing of infected wounds.
[0051] In summary, the dual-network piezoelectric inductive hydrogel of this invention possesses excellent mechanical strength, stable piezoelectric effect, and comprehensive anti-infection function. It can overcome the bottleneck problem of existing hydrogel materials in the treatment of complex infected wounds, and provides a new and efficient material solution for the comprehensive treatment of infected chronic wounds, with significant application prospects and clinical translational value.
[0052] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A method for preparing a dual-network piezoelectric responsive hydrogel having a piezoelectric effect, characterized by, Comprising the following steps: ACG and GelMA as the base material, MBA as the crosslinking agent, combined with the photoinitiator, free radical polymerization was initiated by ultraviolet irradiation to form a precursor solution; BTO nanoparticles were dispersed in the system, and the double network piezoelectric responsive hydrogel ACG-Gel-BTO was prepared by solidification after sufficient mixing.
2. The production method according to claim 1, characterized by, The ACG is obtained by the following preparation method: glycine is dissolved in potassium hydroxide solution, cooled in an ice water bath, then acryloyl chloride is slowly added to the mixture, stirred at room temperature, washed, adjusted pH, extracted, dried, concentrated to obtain the ACG.
3. The preparation method according to claim 1, characterized in that, The BTO is obtained by the following preparation method: Tetrabutoxytitanium is dissolved in anhydrous ethanol, after sufficient mixing, ammonia solution is quickly added and stirred vigorously to hydrolyze tetrabutoxytitanium to form a white sol; According to the predetermined barium-titanium ratio, barium hydroxide monohydrate is weighed and dissolved in deionized water, the dissolved barium hydroxide solution is mixed with the above white sol, stirred thoroughly at room temperature, triethanolamine is added, and the reaction is carried out at a temperature of 140-200℃, after the reaction is completed, the BTO powder is obtained by washing with glacial acetic acid, deionized water and anhydrous ethanol in turn, drying and grinding.
4. The production method according to claim 3, characterized by, The BTO powder is also subjected to a heat treatment step, which is calcination at 800-1200℃ and cooling in the furnace to obtain the heat-treated BTO powder.
5. The preparation method according to claim 1, characterized in that, The feeding ratio of the ACG, GelMA, MBA and photoinitiator I2959 is 0.1g:0.02g:0.3mL:0.005g.
6. The method of claim 1, wherein, The feeding amount of the BTO is 0.25-0.75% of the precursor solution, calculated as weight percentage. 7.A double network piezoelectric responsive hydrogel with piezoelectric effect prepared by the preparation method of any one of claims 1-6. 8.The use of the double network piezoelectric responsive hydrogel of claim 7 in the preparation of an infectious wound healing drug.